Launaea acanthodes (Boiss) O. Kuntze mediates hepatic glucose metabolism and ameliorates impaired pancreatic function in streptozotocin-induced diabetic rats. (25th March 2021) - Marvibaigi, Mohsen; Hosseini, Seyed Morteza; Amini, Neda
Abstract: Ethnopharmacological relevance: Launaea acanthodes (Boiss.) O. Kuntze is native to semiarid regions of central Iran, traditionally used in the treatment of numerous disorders including diabetes. Aim of the study: The current study aimed to explore hypoglycemic activity of Launaea acanthodes extract in streptozotocin-induced diabetic rats. Furthermore, gene expression study was carried out to examine expression levels of key glucose metabolism-related genes. Methods: For in vitro study, Folin-Ciocalteus, DPPH and aluminum chloride colorimetric assays were used to determine the total phenolic content, antioxidant capacity and total flavonoid content of extracts, respectively. For in vivo study, streptozotocin-induced diabetic Wistar rats were orally administered with metformin (50 mg/kg) and various doses of extracts (100, 200 and 400 mg/kg body weight) for 28 days. Fasting blood glucose, body weight, food and water intake were assessed during the course of treatment. At the end of the intervention, oral glucose tolerance test (OGTT), lipid profile and glycated hemoglobin (HbA1c) were evaluated. Furthermore, functional liver enzymes, oxidative stress markers and histopathology of pancreas were examined. Lastly, quantitative real time polymerase chain reaction (qRT-PCR) was applied to explore the mRNA levels of genes relevant to glucose metabolism in the pancreas and liver tissues of diabetic rats. Results: Based on the in vitro results, the hydroalcoholic extract revealed potential radical scavenging activity and contained highest amount of phenolic and flavonoid. The in vivo results demonstrated that the extract lowered fasting blood glucose level, increased the body weight, restored the alterations in the levels of water and food intake, attenuated HbA1c, improved lipid profile and ameliorated the OGTT in diabetic rats. The extract administration alleviated the histopathological changes in the pancreas, suppressed malondialdehyde (MDA) level and further restored attenuated levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), glutathione peroxidase (GPx) and superoxide dismutase (SOD) in diabetic rats. Analysis of real time PCR data showed that extract administration reversed the expression levels of hepatic glucokinase (GK), phosphenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase). Meanwhile, the extract upregulated the expression level of glucose transporter-2 (GLUT-2) and pancreatic-duodenal homeobox (PDX-1) in diabetic rats. Conclusion: Collectively, the results demonstrate that Launaea acanthodes hydroalcoholic extract exerts hypoglycemic effect possibly via regulating key enzymes of glucose metabolism and ameliorating pancreatic dysfunction through its antioxidant properties. Graphical abstract: Image 1 Highlights: Launaea. acanthodes extract showed beneficial effects on glycemic indices. L. acanthodes extract improved lipid profile and pancreatic dysfunction. Extract attenuated streptozotocin-induced oxidative stress in hyperglycemic rats. L. acanthodes extract mediated hepatic glucose metabolism.